Plasma metabolomic and inflammatory profiles associated with low physical function in heart failure: an integrated cardiac–metabolic–muscular phenotype - Konstantinos Prokopidis; Sima Jalali Farahani; Beyza Gulsah Altinpinar; Omid Khaiyat; Adam Burke; Amy Nortcliffe; Gregory Y. H. Lip; Rajiv Sankaranarayanan; Howbeer Muhamadali; Masoud Isanejad (GeroScience, 2026)

Skeletal muscle metabolomic markers underlying the enhanced exercise-induced hypertrophy response to resistance training in older adults - Changhyun Lim; Manoel Lixandrão; Dakshat Trivedi; Yun Xu; Konstantinos Prokopidis; Hamilton Roschel; Stuart M. Phillips; Howbeer Muhamadali; Masoud Isanejad (GeroScience, 2026)
Resistance training (RT) is an effective intervention for improving muscle health and metabolism in ageing, but the degree of responsiveness (hypertrophy) to RT varies substantially. We examined muscle metabolomic profiles before and after 10-weeks RT in older adults classified into upper (UPPER) and lower (LOWER) tertiles of hypertrophy to identify key metabolic adaptation differences. Fifty older adults (23 males, 27 females, mean 68.2 years old) completed 10 weeks of RT combined with whey protein supplementation. Quadriceps cross-sectional area (CSA) was assessed via magnetic resonance imaging before and after RT. Participants were grouped into UPPER (n = 25, 10.3 ± 2% CSA increase) or LOWER (n = 25, 3.3 ± 2% CSA increase) based on ranked CSA changes. We profiled skeletal muscle tissues from the UPPER and LOWER groups using a metabolomics platform. Over 2,500 metabolites were mapped to 104 metabolic pathways. In the UPPER group, upregulation of tryptophan-indole metabolites and the kynurenine pathway suggests a potential role of gut function and anti-inflammatory effect on RT-induced hypertrophy. Also, leucine, isoleucine and valine were significantly upregulated in the absence of their catabolites. Enrichment of urea cycle/amino group metabolism alongside mitochondria-matrix metabolites in the UPPER group indicates improved amino acids and energy homeostasis. Our findings highlight distinct RT-induced skeletal muscle metabolic profiles between UPPER and LOWER in older adults, underscoring the value of metabolic data. These metabolic pathways are important for understanding what contributes to the heterogeneity of hypertrophic response to RT in older adults. Graphical Abstract